Does GPER1 Play a Role in Sexual Dimorphism? - Dovey, Janine L.; Vasudevan, Nandini (Frontiers in Endocrinology, 2020)
Estrogens are critical in driving sex-typical social behaviours that are ethologically relevant in mammals. This is due to both production of local estrogens and signaling by these ligands, particularly in an interconnected set of nuclei called the social behavioural network (SBN). The SBN is a sexually dimorphic network studied predominantly in rodents that is thought to underlie the display of social behaviour in mammals. Signalling by the predominant endogenous estrogen, 17β-estradiol, can be either via the classical genomic or non-classical rapid pathway. In the classical genomic pathway, 17β-estradiol binds the intracellular estrogen receptors (ER) α and β which act as ligand-dependent transcription factors to regulate transcription. In the non-genomic pathway, 17β-estradiol binds a putative plasma membrane ER (mER) such as GPR30/GPER1 to rapidly signal via kinases or calcium flux. Though GPER1’s role in sexual dimorphism has been explored to a greater extent in cardiovascular physiology, less is known about its role in the brain. In the last decade, activation of GPER1 has been shown to be important for lordosis and social cognition in females. In this review we will focus on several mechanisms that may contribute to sexually dimorphic behaviors including the colocalization of these estrogen receptors in the SBN, interplay between the signaling pathways activated by these different estrogen receptors, and the role of these receptors in development and the maintenance of the SBN, all of which remain underexplored.